DAMPAK PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI PERDESAAN TERHADAP PENDAPATAN PETANI DESA PASLATEN, KECAMATAN TATAPAAN, KABUPATEN MINAHASA SELATAN - Anggita ., Nonoy; Eyverson ., Ruauw; Ribka M. Kumaat (Sam Ratulangi University, 2017)
This study aims to determine the impact of the PNPM Mandiri activities to the income of farmers. Research conducted in September through December 2016. The data used are primary data obtained through interviews to 20 (twenty) of the respondents in this case women's credit group (SPP) through the list of questions regarding before and after participating in PNPM-MP and secondary data obtained from the District Office and the Office of Paslaten Tatapaan Sub-district. Analysis of the data used is the analysis kuantitattif using different test average by using the formula paired samples t-test. The results showed PNPM-MP have a positive impact where the income of farmers increasing from Rp.70,663,000 with an average of Rp. 3,533.150 to Rp. 126,397,250 with an average Rp.6,319,862.50,- so that it increases 78.87 %. Therefore this program can help in agriculture where it has been increasing farmers' income after the program PNPM-MP so farmers can expand their farming land.Keywords : National Community Empowerment Program (PNPM-MP), Farmer Income, Paslaten Village, Sub-district of Tatapaan, South Minahasa District